Digital inclusion analysis for Brazil’s unified health system - da Silva Ferreira, Shirley Karolina; Sene Junior, Iwens Gervasio (Journal of Health Informatics, 2023)
Objective: Analyzes the coverage of the digital inclusion programs in health units. Method: The public data of the Cidades Digitais and Wi-fi Brasil programs were analyzed, extracting the number and type of health units supported by the programs, for each Brazilian region and state. Results: The North and Northeast regions have the largest number of health units attended by the programs. The collected data shows that 4.4% of the Wi-fi Brasil’s total access points are in health units and mainly in Indigenous Health Centers (28%), whilst Cidades Digitais corresponds to 4.3%, supporting the Basic Health Units (33%). Conclusion: To recognize the community’s level of access to the internet it is important to propitiate the digital inclusion in health units and then contribute to the National Health Data Network, following the Digital Health Strategy 2020-2028 guidelines.